Text mining and it is development stages - Samiyeva, Maftuna Faxriddin qizi; Madyarova, Mukhlisa Abdulla qizi (Science and Education, 2023)
This paper is based on the process of designing text mining. And it illustrates how social mining is increasing in the ICT sector.